The role of Ukrainian education in the formation of modern values: attitudes of experts and youth - Левін, Р. Я.; Середа, Ю. В. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2015)
It was demonstrated that Ukrainian youth - "independence generation", a "new product" of the national education, holds better modernization potential than the rest of society; however, according to experts, the Ukrainian educational system is not effective enough in terms of modern values production. It was determined that the key reason of mismatch between education and actual values relates to the professional deformation of school teacher due to the low efficiency of selection system, training, promotion and professional development.